2018
DOI: 10.1111/jspn.12208
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a biomedical device (VeinViewer®) to assist with peripheral intravenous catheter (PIV) insertion for pediatric nurses

Abstract: The ongoing need for resources focused on building nurse skills and confidence for PIV insertion was highlighted and organizations should continue to direct efforts toward developing skills and competency for staff that are responsible for pediatric vascular access. This study illustrates the importance of data-driven decision-making for expensive hospital-funded equipment purchases. This nursing led research study highlights how perceptions do not always align with outcomes. The lessons gleaned from this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Standards for PIVC care were developed using published recommendations for best practice based on existing evidence, clinical applicability and economic impact (Table 1) (Cuper et al, 2013;Demir & Inal, 2019;McNeely, Ream, Thrasher, Dziadkowiec, & Callahan, 2018). The importance of the PIVC dressing and securement is emphasized in numerous study findings (Hetzler, Wilson, Hill, & Hollenback, 2011;Hugill, 2016;Kleidon et al, 2017;Kleidon, Cattanach, Mihala, & Ullman, 2019;Watterson et al, 2018).…”
Section: Standardizing Procedures and Educationmentioning
confidence: 99%
“…Standards for PIVC care were developed using published recommendations for best practice based on existing evidence, clinical applicability and economic impact (Table 1) (Cuper et al, 2013;Demir & Inal, 2019;McNeely, Ream, Thrasher, Dziadkowiec, & Callahan, 2018). The importance of the PIVC dressing and securement is emphasized in numerous study findings (Hetzler, Wilson, Hill, & Hollenback, 2011;Hugill, 2016;Kleidon et al, 2017;Kleidon, Cattanach, Mihala, & Ullman, 2019;Watterson et al, 2018).…”
Section: Standardizing Procedures and Educationmentioning
confidence: 99%
“…reported that the nurses felt positively about the requirement of a biomedical device for assistance in intravenous access though their study did not demonstrate any significant difference in outcome. [ 15 ] It can be contemplated that experienced phlebotomists may not find much use for this device due to their experience as seen in Szmuk et al . [ 7 ] Whether newer workers and trainees may benefit more from this device is yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from a recent randomized controlled trial demonstrated that these devices did not improve IV placement success. Moreover, the authors advocated for building nurses' skills and confidence in IV insertion (McNeely, Ream, Thrasher, Dziadkowiec, & Callahan, 2018).…”
Section: Discussionmentioning
confidence: 99%